Identification of broadleaf and coniferous trees as a primary source of acrolein - Ehrlich, Johnnie; Cahill, Thomas M. (Atmospheric environment (1994), 2018)
Ambient atmospheric acrolein is commonly associated with anthropogenic combustion sources, but there is increasing evidence that acrolein has a non-combustion natural source that contributes to a low, natural background of acrolein in remote regions. The objective of this research was to determine the presence of acrolein in a probable natural source, namely decaying leaf litter in forests. The first phase of this project surveyed leaf litter under five conifer and eight broadleaf tree species to determine whether acrolein could volatilize from the biomass that was present. Acrolein was detected in all species, but the concentrations were higher in recently dropped biomass. The second phase of the project measured the changes in acrolein concentration during the decomposition of fresh foliar biomass. The results showed a dramatic decline in acrolein and other aldehydes during the first two weeks of composting. The last phase of the project directly extracted fresh leaves and demonstrated that the fresh foliar biomass had high concentrations of acrolein even when there was no opportunity for microbial degradation. Taken together, these results suggest that the plants were primarily responsible for the production of acrolein which then subsequently volatilized or decayed when the foliar biomass was dropped from the tree. This research demonstrated that acrolein can be produced by plants, which provides a source of acrolein that can contribute to the natural background of acrolein in remote areas. In many cases, this natural background exceeds the EPA's reference concentration for acrolein. [Display omitted] •Acrolein was detected in forest leaf litter from diverse species of plants.•The concentrations of aldehydes in leaf mulch drop quickly as it ages.•Acrolein was detected in fresh, green biomass that was not subject to decomposition.•Identification of a natural acrolein source partly explains the observed natural background.